Circadian Differences in the Contribution of the Brain Renin-Angiotensin System in Genetically Hypertensive Mice - Jackson, Kristy L.; Marques, Francine Z.; Lim, Kyungjoon; Davern, Pamela J.; Head, Geoffrey A. (Frontiers in Physiology, 2018)
Objective: Genetically hypertensive BPH/2J mice are recognised as a neurogenic model of hypertension, primarily based on sympathetic overactivity and greater neuronal activity in cardiovascular regulatory brain regions. Greater activity of the central renin angiotensin system (RAS) and reactive oxygen species (ROS) reportedly contribute to other models of hypertension. Importantly the peripheral RAS contributes to the hypertension in BPH/2J mice, predominantly during the dark period of the 24hr light cycle. The aim of the present study was to determine whether central AT1 receptor stimulation and the associated ROS signalling contribute to hypertension in BPH/2J mice in a circadian dependent manner. Methods: Blood pressure (BP) was measured in BPH/2J and normotensive BPN/3J mice (n=7-8) via pre-implanted telemetry devices. Acute intracerebroventricular microinjections of AT1 receptor antagonist, candesartan, and the superoxide dismutase mimetic, tempol, were administered during the dark and light period of the 24hr light cycle via pre-implanted intracerebroventricular guide cannula. In separate mice, the BP effect of intracerebroventricular infusion of the AT1 receptor antagonist losartan for 7 days was compared with subcutaneous infusion to determine the contribution of the central RAS to hypertension in BPH/2J mice. Results: Candesartan administered ICV during the dark period induced depressor responses which were 40% smaller in BPH/2J than BPN/3J mice (Pstrain<0.05), suggesting AT1 receptors stimulation may contribute less to BP maintenance in BPH/2J mice. During the light period candesartan had minimal effect on BP in either strain. Intracerebroventricular tempol had comparable effects on BP between strains during the light and dark period (Pstrain>0.08), suggesting ROS signalling is also not contributing to the hypertension in BPH/2J mice. Chronic intracerebroventricular administration of losartan (22nmol/hr) had minimal effect on BPN/3J mice. By contrast in BPH/2J mice, both intracerebroventricular and subcutaneously administered losartan induced similar hypotensive responses (-12.1±1.8 vs -14.7±1.8mmHg, Proute=0.31). Conclusion: While central effects of peripheral losartan cannot be excluded, we suggest the hypotensive effect of chronic ICV losartan was likely peripherally mediated. Thus, based on both acute and chronic AT1 receptor inhibition and acute ROS inhibition, our findings suggest that greater activation of central AT1 receptors or ROS are unlikely to be mediating the hypertension in BPH/2J mice.